2018
DOI: 10.1007/s10068-018-0317-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of β-lactamase- and efflux pump-mediated multiple antibiotic resistance in Salmonella Typhimurium

Abstract: This study aimed to assess the β-lactamase- and efflux pump-mediated antibiotic resistance in Typhimurium (WT-ST), ciprofloxacin-induced antibiotic-resistant. Typhimurium (CI-ST), and clinically-acquired antibiotic-resistant . Typhimurium (CA-ST). The β-lactamase activities were significantly increased up to 63 μmol/min/mL in CA-ST and 24 μmol/min/mL in CI-ST when compared to WT-ST (13 μmol/min/mL). The highest efflux pump activity was observed in CI-ST and CA-ST, showing more than 45%. The antibiotic suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Furthermore, there exists a correlation between multidrug efflux pumps and biofilm in Salmonella, as biofilm formation is compromised upon deletion or inhibition of multidrug efflux pumps (51). Our data suggests that on September 10, 2020 at GESELLSCHAFT FUR BIOTECHNO-http://iai.asm.org/ Downloaded from the gene for the multidrug efflux transporter MdtM is upregulated, which can be an innate resistance mechanism as upregulation of efflux pumps confers multiple drug resistance in bacteria (52). It has been previously shown that a csgD deletion mutant accumulates tricarboxylic (Krebs) cycle intermediates in order to block gluconeogenesis.…”
Section: Several Other Effects Of Clarithromycin Might Contribute To mentioning
confidence: 69%
“…Furthermore, there exists a correlation between multidrug efflux pumps and biofilm in Salmonella, as biofilm formation is compromised upon deletion or inhibition of multidrug efflux pumps (51). Our data suggests that on September 10, 2020 at GESELLSCHAFT FUR BIOTECHNO-http://iai.asm.org/ Downloaded from the gene for the multidrug efflux transporter MdtM is upregulated, which can be an innate resistance mechanism as upregulation of efflux pumps confers multiple drug resistance in bacteria (52). It has been previously shown that a csgD deletion mutant accumulates tricarboxylic (Krebs) cycle intermediates in order to block gluconeogenesis.…”
Section: Several Other Effects Of Clarithromycin Might Contribute To mentioning
confidence: 69%
“…MDR bacteria use multiple mechanisms to overcome the action of antimicrobials, such as active efflux or enzymatic degradation of the antimicrobial, mutation of an antimicrobial target site, and reduced cell wall permeability [41][42][43]. In Salmonella, the most common efflux pump system, belonging to the RND family is the AcrAB-TolC, responsible for resistance to various antibiotics [44]. Likewise, we observed efflux activity in the tested Salmonella isolates, which might explain their strong resistance to several tested antibiotics (Supplementary Section S2; Figure S1a).…”
Section: Discussionmentioning
confidence: 99%
“…All tested bacterial isolates, except for S. hyicus M48 were positive for beta-lactamase enzyme activity. Beta-lactamase enzyme activity coded by blaZ genes has been reported in AMR Staphylococcus strains [44], while that in Salmonella has been associated with genes of bla TEM, bla CTX-M , bla SHV, bla OXA-1 , and bla CMY-2 [44]. H 2 S production in bacteria is vital for protection against antibiotic-induced damage and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…This involves reducing the number of porin channels in the outer membrane of bacteria, thereby limiting the ability of β-lactam molecules to enter the cell space. Another mechanism involves actively pumping the drug out of the bacterial cell, which can be intensified by an increase in the expression of efflux pump and porin systems, which are responsible for this process [ 204 ]. Another mechanism involves production of β-lactamases, which are specific enzymes catalyzing the hydrolysis of the β-lactam ring in the molecule of the drug [ 205 ].…”
Section: Mechanisms Of Transfer Of Resistance Based On Examples Of Va...mentioning
confidence: 99%